Association between dietary zinc intake and Helicobacter pylori seropositivity in US adults: National Health and Nutrition Examination Survey - Zhang, Kai; Han, Yu; Gu, Fangming; Gu, Zhaoxuan; Zhao, JiaYu; Chen, Jianguo; Chen, Bowen; Gao, Min; Hou, Zhengyan; Yu, Xiaoqi; Cai, Tianyi; Gao, Yafang; et al. (Frontiers in Nutrition, 2023)
Purpose: Helicobacter pylori infection is a well-established etiological factor for gastric inflammation and a significant risk factor for the development of gastric cancer. However, the precise relationship between dietary zinc intake and seropositivity for Helicobacter pylori remains uncertain. Methods: This cross-sectional observational study utilized data from the United States National Health and Nutrition Examination Survey conducted between 1999 and 2000. The study cohort comprised 2,884 adults aged 20 years or older who provided comprehensive 24-hour dietary recall data. The presence of Helicobacter pylori infection was confirmed using serum analysis and lgG protein enzyme-linked immunosorbent assay (ELISA). Multivariable logistic regression models and generalized additive model (GAM) were employed to explore the potential association between dietary zinc intake and Helicobacter pylori seropositivity. Results: Additionally, subgroup analysis was performed to evaluate the robustness of the primary findings. Of the 1,281 participants, 47.8% were male and the average age was 49.5 years. In the fully adjusted model, a statistically significant inverse association between dietary zinc intake and Helicobacter pylori seropositivity was observed [quartile variable, Q4 vs. Q1, odds ratio (OR): 0.72, 95% confidence interval (CI): 0.57-0.91, p = 0.007]. Furthermore, the relationship between dietary zinc intake and Helicobacter pylori seropositivity exhibited an L-shaped pattern, indicating a saturation effect. The results of sensitivity analysis remained consistent and reliable. Conclusion: Therefore, this study suggests that higher dietary zinc intake may be associated with a lower prevalence of Helicobacter pylori seropositivity. Notably, this association follows an L-shaped pattern, with a threshold point estimated at 24.925 mg/day.